2013 IEEE International Conference on Granular Computing (GrC) 2013
DOI: 10.1109/grc.2013.6740450
|View full text |Cite
|
Sign up to set email alerts
|

The design of touch-screen with high resolution infrared based on plastic optical fiber and image processing

Abstract: Main defects of infrared touch screen are low resolution and sensors to be easily damage, which makes it can't realize the accurate positioning. To overcome infrared screen principle inherent defects, we propose a new solution by the principle of innovation, with a laser tube instead of the infrared emission tube, plastic optical fiber instead of the infrared receiver, CMOS sensor instead of complex circuits, which resulting a design of touch-screen with high resolution infrared based on plastic optical fiber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Recent results have demonstrated that carbon coating is primarily dependent on the carbon source. Therefore, various carbon sources have been employed for carbon-coated LVP, such as glucose [12,40,85,[107][108][109], sucrose [110][111][112], maltose [113], citric acid [47,[114][115][116], starch [117], carbon black [118], EDTA [119], PS spheres [71,120], β-cyclodextrin [121], carboxy methyl cellulose (CMC) [122], PEG-400 [123], and PEG-10,000 [124], etc.…”
Section: Carbon Coatingmentioning
confidence: 99%
“…Recent results have demonstrated that carbon coating is primarily dependent on the carbon source. Therefore, various carbon sources have been employed for carbon-coated LVP, such as glucose [12,40,85,[107][108][109], sucrose [110][111][112], maltose [113], citric acid [47,[114][115][116], starch [117], carbon black [118], EDTA [119], PS spheres [71,120], β-cyclodextrin [121], carboxy methyl cellulose (CMC) [122], PEG-400 [123], and PEG-10,000 [124], etc.…”
Section: Carbon Coatingmentioning
confidence: 99%